Efficacy of the antioxidants BHA and BHT in palm olein during heating and frying - Augustin, M. A.; Berry, S. K. (Wiley, 1983)
The effectiveness of butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) in retarding the deterioration of RBD palm olein during static heating (180 C) and frying operations was assessed by determining the peroxide, anisidine, acid and iodine values; absorbances at 232 and 268 nm; and the fatty acid composition of the oil. During static heating of the oil, BHA was found to be a more effective antioxidant than BHT whereas, during intermittent frying of potato chips, both the antioxidants were relatively ineffective in retarding the deterioration of the oil. The loss of BHT from the oil during static heating exceeded that of BHA. On the other hand, when potato chips were fried in the oil periodically, a higher loss of BHA was observed.